Penerapan Teknik Ecoprint pada Kain Katun untuk Pembuatan Vest - Nisa, Atina Khoiron; Dasining, Dasining; Hidayati, Chairunisa Wiji; Mawadah, Vina Laili (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The ecoprinting technique, which employs a method of directly imparting color and shape to fabric, is one of the new discoveries that have led to the development of the natural material dyeing technique. The foundation for supporting appearance is outer. There are many different types of outerwear made, such as vests, blazers, and jackets. Worn either after a shirt or before a jacket, a vest completes the outfit. There are two different lengths of vests: one that falls below the breasts and the other that falls between the waist and the hips. The purpose of this study is to identify the ecoprint method that uses alum and tunjung mordant as well as how vests are made using this method on cotton fabric. The natural ingredients consist of kenikir leaves, meat crumble leaves, waru flowers, and bridal tears flowers. The outcome showed that while the motif was good, it was disorganized and some motifs were hidden because the fabric had been folded during the rolling process.